2007
DOI: 10.1038/sj.ejcn.1602644
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of nutrient intake in pregnancy: effects on infant measures and possible influence on diseases related to season of birth

Abstract: Objectives: To determine, firstly, if there was any seasonal effect on nutrient intake during pregnancy and birth measures, secondly, if there was any relationship between maternal nutrient intake and infant birth measures according to season and thirdly, to consider the hypothesis that seasonal change in nutrient intake during pregnancy might affect health in later life of some women's offspring. Design: Pilot study to determine number of days required to characterize group intake followed by a prospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 62 publications
6
72
0
Order By: Relevance
“…Vitamin D may be a surrogate marker for other causative factors that vary between populations, particularly those with (35) . A recent study has demonstrated seasonal variation in gene expression in human lymphocytes and adipocytes (36) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin D may be a surrogate marker for other causative factors that vary between populations, particularly those with (35) . A recent study has demonstrated seasonal variation in gene expression in human lymphocytes and adipocytes (36) .…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of the vitamin D nuclear receptor and vitamin D binding protein have been associated with a wide variety of conditions (33,34) , and may explain why a study in the USA found that vitamin D deficiency (<37·5 nmol/l) was a risk factor for SGA in white women (adjusted OR 7·5; 95 % CI 1·8, 31·9) but not in black women (adjusted OR 1·5; 95 % CI 0·6, 3·5) (28) . This study found a non-linear association between 25-hydroxyvitamin D concentration and SGA, with an increased risk of SGA with concentrations >75 nmol/l (OR 2·2; 95 % CI 1·2, 3·8).Vitamin D may be a surrogate marker for other causative factors that vary between populations, particularly those with (35) . A recent study has demonstrated seasonal variation in gene expression in human lymphocytes and adipocytes (36) .…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This is true because in decades past there were important seasonal differences in nutrition, especially in developing countries such as Ukraine. These differences in access to high-quality food supply can potentially influence intrauterine growth, depending on the month of gestation [2]. Other possible triggering factors for developing type 2 diabetes, such as production of vitamin D [3] and outdoor temperature [4], also tend to change seasonally.…”
mentioning
confidence: 99%
“…Considering that adult health might be programmed early in life, it is interesting to study the nutritional basis for effects of maternal diet on the offspring. Previous studies have investigated how a variety of nutritional compounds including fish oils, 19,20 vitamins, [21][22][23] minerals 24 and macronutrients 25,26 may affect offspring phenotype, but most studies have concerned protein composition in the mother's diet during pregnancy or lactation and obesity risk of offspring. 4,12,27,28 In this study, we investigate how variation in protein to carbohydrate balance of maternal food before mating affects fat deposition of adult offspring mice.…”
Section: Introductionmentioning
confidence: 99%